2016
DOI: 10.1021/acsmacrolett.6b00235
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Mediated Polymerization-Induced Self-Assembly in the Absence of External Catalyst or Initiator

Abstract: Benzyl methacrylate (BzMA, Aldrich) was deinhibited by passing through a column of basic alumina.Oligo(ethylene glycol) methyl ether methacrylate (OEGMA) (M n = 300 g mol -1 ) (Sigma-Aldrich) was used as received. 2,2'-azobis(isobutyronitrile) (AIBN, Fluka, 98%) was purified by recrystallization from methanol. 4-Cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl] pentanoic acid (CDTPA, Boron Molecular) was used as received. All other reagents were used as received unless otherwise specified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 74 publications
6
169
0
3
Order By: Relevance
“…SEC‐measured dispersities, Ð, ranged between 1.33 and 1.58, somewhat higher than expected for RAFT polymerization, which was attributed to possible cross‐linker impurities in the commercial PEGMA monomer. Similarly high dispersities have been reported for PISA formulations using pPEGMA as the stabilizing block . A summary of all nanoparticles with compositions, SEC data, and hydrodynamic diameters (measured by dynamic light scattering [DLS]) is given in Table S3, Supporting Information.…”
Section: Resultssupporting
confidence: 54%
“…SEC‐measured dispersities, Ð, ranged between 1.33 and 1.58, somewhat higher than expected for RAFT polymerization, which was attributed to possible cross‐linker impurities in the commercial PEGMA monomer. Similarly high dispersities have been reported for PISA formulations using pPEGMA as the stabilizing block . A summary of all nanoparticles with compositions, SEC data, and hydrodynamic diameters (measured by dynamic light scattering [DLS]) is given in Table S3, Supporting Information.…”
Section: Resultssupporting
confidence: 54%
“…The development of controlled/living radical polymerization (CLRP, also known as reversible deactivation radical polymerization [RDRP]) has revolutionized our ability to prepare polymeric nanoparticles of various morphologies . Polymerization‐induced self‐assembly (PISA), most commonly based on reversible addition‐fragmentation chain transfer (RAFT) polymerization, has emerged as a useful method for synthesis of a wide range of nanoparticle morphologies. More recently, PISA has been expanded to approaches based on nonliving radical polymerization (addition‐fragmentation chain transfer polymerization), photo‐induced CLRP, as well as ring‐opening metathesis polymerization .…”
Section: Methodsmentioning
confidence: 99%
“…These advances pave the road for the synthesis of vesicles through photo‐PISA. More interestingly, recently, it has been reported that photo‐PISA can also be initiated in the absence of either photoinitiator or photocatalyst because the RAFT agent itself can generate radicals under light radiation which can activate the polymerization . The morphology of the resulting photo‐PISA products is related to the wavelength of the light used.…”
Section: Pisa An Ex Novo Strategy For Vesicle Formation Growth Andmentioning
confidence: 99%